Peranan Guru Dalam Implementasi Trilogi Ki Hajar Dewantara Terhadap Pembentukan Karakter Siswa di MA Roudlatul Muta’abbidin Lamongan - Ikmal, Hepi; Mumtahana, Lusia; Budiantoro Fialriyadi, Mohammad (Universitas Yudharta Pasuruan, 2022)
This research seeks to explore and interpret the role of teachers in the implementation of the Ki Hajar Dewantara Trilogy towards the formation of student character in MA Roudlotul Muta'abbidin Solokuro Lamongan. Using a qualitative approach, this study uses data mining techniques in the form of interviews, observations, and documentation, the results of this study, describe the role of teachers in the implementation of the Ki Hajar Dewantara trilogy towards the formation of student character in MA Roudlotul Muta'abbidin into three components, namely in the capacity as Ing Ngarsa Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani in student formation. The three will be detailed in this study as the spirit of the Ki Hajar Dewantara trilogy and based on the findings of data in the field.